2008
DOI: 10.1111/j.1574-6968.2008.01176.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide production by Lactobacillus johnsonii NCC 533 and its role in anti-Salmonella activity

Abstract: The human intestinal isolate Lactobacillus johnsonii NCC 533 (La1) is a probiotic strain with well-documented antimicrobial properties. Previous research has identified the production of lactic acid and bacteriocins as important factors, but that other unidentified factors are also involved. We used the recently published genome sequence of L. johnsonii NCC 533 to search for novel antipathogen factors and identified three potential gene products that may catalyze the synthesis of the known antimicrobial factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
91
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(92 citation statements)
references
References 31 publications
0
91
0
Order By: Relevance
“…The antimicrobial effect of lactic acid is not just due to the lowering of the intracellular pH. Indeed, hydrogen peroxide produced by L. johnsonii NCC 533 and other L. johnsonii strains in vitro kills S. Typhimurium (133), an effect enhanced in the presence of the membrane permeabilizer lactic acid (132). As deduced from in vitro experiments that have tested the sensitivities of secreted compounds present in L. rhamnosus GG, L. johnsonii NCC 533, and L. acidophilus LB CFCSs to a set of physical and chemical treatments and from partial isolation experiments, bactericidal activity against S. Typhimurium results from small (dialysis cutoff, 1,000 Da), nonproteinaceous compounds (120,122,123).…”
Section: Direct Activities Against Enterovirulent Bacteriamentioning
confidence: 99%
“…The antimicrobial effect of lactic acid is not just due to the lowering of the intracellular pH. Indeed, hydrogen peroxide produced by L. johnsonii NCC 533 and other L. johnsonii strains in vitro kills S. Typhimurium (133), an effect enhanced in the presence of the membrane permeabilizer lactic acid (132). As deduced from in vitro experiments that have tested the sensitivities of secreted compounds present in L. rhamnosus GG, L. johnsonii NCC 533, and L. acidophilus LB CFCSs to a set of physical and chemical treatments and from partial isolation experiments, bactericidal activity against S. Typhimurium results from small (dialysis cutoff, 1,000 Da), nonproteinaceous compounds (120,122,123).…”
Section: Direct Activities Against Enterovirulent Bacteriamentioning
confidence: 99%
“…Several studies have speculated on the effect that H 2 O 2 may exert on the host as well as on the microbiome. Some authors propose that it can directly damage the epithelium (23,24) and cause cell death of other bacteria (5,7). Others suggest that H 2 O 2 accumulation may contribute to the maintenance of a normal and homeostatic microbiota.…”
mentioning
confidence: 99%
“…Some of these H 2 O 2 -forming species are opportunistic pathogens or pathobionts, such as Streptococcus pyogenes (1), Streptococcus mutans (2,3), and Streptococcus pneumoniae (4,5). Other H 2 O 2 -producing species or strains have been proposed to have probiotic properties, such as Bifidobacterium bifidum (6) and Lactobacillus johnsonii (7), or are prevalent in the commensal vaginal microbiota, such as Lactobacillus crispatus, Lactobacillus jensenii, and Lactobacillus gasseri (8).…”
mentioning
confidence: 99%
“…In addition, we found that lactic acid by its membrane permeabilization activity (Alakomi et al, 2000;Liévin-Le Moal et al, 2011) participates in the LcS CFCS inhibitory activity against both S. Typhimurium SL1344 and H. pylori 1101 swimming motilities. For the killing activity of hydrogen peroxide against Gardnerella vaginalis, uropathogenic E. coli and S. Typhimurium (Atassi & Servin, 2010; Pridmore et al, 2008), lactic acid acts cooperatively by increasing the sensitivity of target bacteria (Atassi & Servin, 2010). It is tempting to propose that lactic acid secreted by the strain LcS through an increase of membrane permeability favours the entry within the target pathogens of secreted compound(s) that block swimming motility.…”
Section: Discussionmentioning
confidence: 99%